Does warming up with wearable resistance influence internal and external training load in national level soccer players? - Uthoff, A.; Bustos, A.; Metral, G.; Cronin, J.; Dolcetti, J.; Rumpf, M. C. (Sports Health: A Multidisciplinary Approach, 2022)
Background: Adding wearable resistance (WR) to training results in superior performance compared with unloaded conditions. However, it is unclear if adding WR during warm-up influences training load (TL) in the subsequent session. The aim of this research was to track TL in soccer players during the transition from late preseason to early in-season and examine whether adding WR to the lower leg during a warm-up influenced TL measures during warm-ups and on-field training sessions after WR was removed. Hypothesis: The addition of WR worn on the lower legs during an on-field warm-up would lead to decreases in relatively high-intensity external TL metrics, such as distance covered >6.11 m/s and acceleration and deceleration >/<3 m/s² and increases in internal TL during the warm-up, yet would have little effect on the subsequent training session when WR was removed. Study Design:Matched-pair randomized design. Level of Evidence: Level 3. Methods: A total of 28 soccer players were allocated to either a WR training (WRT = 14) or unloaded (control [CON] = 14) group. Both groups performed the same warm-up and on-field training for 8 weeks, with the WRT group wearing 200 g to 600 g loads on their lower leg during the warm-up. External TL was measured via global positioning system data and internal TL was assessed using session rating of perceived exertion (sRPE × time per session). Results: No statistically significant between-group differences (P = 0.05) were identified for any TL measurement during either warm-ups or training sessions. Lower leg WR resulted in trivial to moderate effects for all external TL metrics (-16.9% to 2.40%; d = -0.61 to 0.14) and sRPE (-0.33%; d = -0.03) during the warm-up and trivial to small effects on all external TL metrics (-8.95% to -0.36%; d = -0.45 to -0.30) and sRPE (3.39%; d = 0.33) during training sessions. Conclusion: Warming up with lower leg WR negatively affects neither the quality and quantity of the warm-up nor the subsequent training session once WR is removed. Clinical Relevance: Using WR on the lower leg during on-field warm-ups may be a means to "microdose" strength training while not unduly increasing TL. However, further research is needed to determine the influence of WR on strength qualities.